2019
DOI: 10.1186/s12974-019-1610-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential link between the RagA-mTOR-p70S6K axis and depressive-behaviors during bacterial liposaccharide challenge

Abstract: BackgroundBacterial infection is a potential risk factor for depression. However, little is known about the mechanistic link between bacterial endotoxin and depressive-like behaviors. The aim of the present study was to clarify whether liposaccharide (LPS) could induce depressive-like behaviors in mice via sequentially activating small GTPase RagA, mammalian target of rapamycin (mTOR), and p70S6K.MethodsC57BL/6 N mice were treated with 0.83 mg/kg LPS by intraperitoneal injection for 24 h. The animals were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…In liposaccharide-treated mice expressing all phenotypic features of depression, mTOR/p70S6K signaling was elevated in the brain homogenate. Similar findings were observed in in vitro studies using cortical and stem cell neurons [53]. These findings implicate this pathway in the complex pathological mechanism of depression.…”
Section: Neurochemical Cascades and Other Mechanismssupporting
confidence: 87%
“…In liposaccharide-treated mice expressing all phenotypic features of depression, mTOR/p70S6K signaling was elevated in the brain homogenate. Similar findings were observed in in vitro studies using cortical and stem cell neurons [53]. These findings implicate this pathway in the complex pathological mechanism of depression.…”
Section: Neurochemical Cascades and Other Mechanismssupporting
confidence: 87%
“…Thus, LPS was used to induce acute inflammation and depressive-like behaviors in mice [ 37 ]. Indeed, we recently found that LPS could cause the depressive-like behaviors in mice via activating RagA/mTOR/p70S6K pathway [ 8 ]. As for the therapy of depression, the conventional antidepressant drugs are challenged by gastrointestinal and sexual side effects [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently revealed that LPS markedly upregulated RagA expression and activated mTORC1 pathway [ 8 ]. RagA forms heterodimers with other isoforms for different functions, for example, RagA/RagB heterodimer for binding GTP and RagC/RagD heterodimer for binding GDP [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations